Israel in the Book of Kings: the past as a project of social identity - Linville, James Richard (The University of Edinburgh, 1997)
The book of Kings provides an expression of social identity for the Persian-era (or perhaps Hellenistic) communities from which Judaism later emerged. Firm historical reconstructions of the book's provenance cannot be derived from a study of the book itself, but its symbolic complexity suggests that it was addressed not only to Judaean readers, but to the Diaspora as well. Its emphasis on themes of 'exile' over 'restoration' suggests the description of its perspective as 'exilicist'.

SECTION ONE: Established historical critical research into Kings is suspect for its contradictory conclusions and too-simple association between literary features and authorial schools of thought. Kings is not profitably studied as a part of a comprehensive history work produced by 'Deuteronomists'. Moreover, a range of dates later than the 6th century dates usually proposed is more probable. E. T. Mullen's 'constructionist' approach fails for want of a radical suspension of established scholarship into Kings. P.R. Davies' more sweeping critique and superior historical context can be adapted, while more attention is drawn to the Diaspora as influencing the composition of the book. The dialectic relationship between social reality and the socially validated history is too complex to permit Kings being seen as an easily penetrated projection of the writer's world onto the monarchic past. Contradiction and paradox are not so much evidence of diachronic composition, but as the result of a necessarily problematic symbolic universe.

SECTION TWO: The schism between Judah and Israel is implicit in the description of the United Monarchy. Symbols of religious legitimacy, such as the 'throne of Israel' and the 'nagid (ruler) of Yahweh's people Israel', however, are traceable through the history of the two kingdoms, despite being unequally distributed between Judah and Israel. They are also symbols of a unified nation. The story of the schism recalls the exodus, and so is cast as a perversion of Israel's origin in which the nation is twice re-born. Judah and Israel are each representative of different aspects of the whole, but the continuing story of the two kingdoms render each one's situation problematic. A level of reconciliation is found through the shared fate of exile, as described in 2 Kgs 17.

SECTION THREE: Josiah's reign is the depiction of the transformation of the people from a 'monarchic' nation to an 'exilic' population, evidenced through the reforms and willing participation of the populace in rituals and ceremonies. Egypt plays a significant role in the closing chapters, being the prototype, and, in some ways, the antithesis of Babylon. It is likely that Kings is recognising the legitimacy of Judaean communities in Egypt. Egypt is also important since the exodus is a major component in King's presentation of Israel's origins. 1 Kings 8 presents the temple site as sacred, not only because of the manifestation of God's presence there, but because it anticipates the eventual exile and destruction of the temple. Solomon's petitions for God's attentiveness to Israel's prayers for forgiveness contrasts with God's portrayal as harsh or arbitrary. This, however, is part of a strategy for a continued communion between God and a dispersed, 'exilic' people, who nonetheless retain cultural autonomy.